The Influence of the Explosive Ordnance Disposal Suit on the Bomb Squad Safety - Michał GMITRZUK; Lech STARCZEWSKI; Krzysztof SZCZEŚNIAK; Dariusz DANIELEWICZ; Robert NYC; Leszek KOSMALA (Problemy Mechatroniki)
The article presents a study on the influence of shock wave on a Hybrid III anthropomorphic test device (ATD HIII) equipped with an explosive ordnance disposal (EOD) suit. The shock wave was generated by the detonation of SEMTEX 1A plastic explosive, formed in the shape of a 250 g, 500 g, and 840 g sphere, at a distance of 0.5 m, 1 m, and 2 m. The use of ATD allowed for determining parameters of damage to the human body as a result of the impact of overpressure wave. The experiments also included a measurement of such parameters as forces and moments on lower extremi-ties, acceleration of head and pelvis, and forces and moments on a neck simulator. Chest Wall Velocity Predictor (CWVP), calculated from the pressure measured on ADT’s chest, was adopted as the most critical parameter. It was revealed that the allowed distance of explosion of a 500 g pure explosive, which does not cause exceeding the allowed parameters, is 1 m.